Android-Based Health Service Center Search Application in Tasikmalaya City Using Location Based Service (LBS) Method - Ramadhan, Muhammad Rizky; Faizah, NM; Koryanto, Lucky (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Health Service is a place to organize health efforts. Not all health service locations are known to the public, both those from Tasikmalaya City and those from outside the city. This is due to a lack of information about health services in the City of Tasikmalaya. Progress and development of the times, as currently the use of technology is needed to be able to provide information quickly, where the use of technology can be accessed anytime and wherever the user is. The use of Information Technology such as using an Android-based Smartphone Application can be used to help citizens to find a location and find out the route to the desired health service. This study aims to build an Android-based Health Service Search application as a source of information to find out the location and routes to service locations. health services in Tasikmalaya City. The research method used is the waterfall process model. Implementation of health service applications using Javascript programming with Android Studio, Location Based Service, and maps sourced from the Google Maps API. The results of the research are in the form of Android-based Tasikmalaya City health service applications that help make it easier for Tasikmalaya City residents and outside the region to obtain information about Health Services and routes from the user's location to the desired Health Service location in Tasikmalaya City with the help of GPS.